BIOLOGIC AGENTS AND CAR T-CELL THERAPY IN SYSTEMIC LUPUS ERYTHEMATOSUS: CURRENT EVIDENCE AND CLINICAL PERSPECTIVES - NARRATIVE REVIEW - Filip Chodań; Estera Sośniecka; Olga Klimczak; Adam Miler; Dagmara Laufer; Krystian Domeracki (Archiv Euromedica, 2026)
Background Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease in which persistent activity, organ damage, glucocorticoid dependence, and treatment toxicity remain challenges. Advances in SLE immunopathogenesis have enabled pathway-targeted therapies, but their evidence and clinical readiness varies. Aim To review established and emerging targeted therapies for SLE, including CAR T cell therapy, with emphasis on mechanisms, efficacy, safety, regulatory status, and clinical roles. Materials and Methods PubMed, Google Scholar, and ClinicalTrials.gov were searched for English-language sources from January 2010 to July 2026. The final search was conducted on 10 July 2026. Earlier landmark and mechanistic sources were included. The synthesis comprised 80 publications and registry records; preclinical evidence informed mechanisms only. Results Targets included B cells, BAFF and APRIL, type I interferon, CD40 and CD40L, plasma cells, FcRn, TLR7 and TLR8, and complement. Belimumab and anifrolumab have established roles in active extrarenal SLE. Evidence supports belimumab and obinutuzumab in lupus nephritis, although evidence maturity differs. Rituximab remains relevant mainly in refractory disease. Approval status varies by agent, indication, and jurisdiction. Most emerging therapies remain investigational. CAR T cell therapy remains experimental but has yielded encouraging results in small uncontrolled studies of severe refractory SLE. Safety profiles differ, and long-term safety data for emerging approaches are limited. Conclusions These approaches differ in regulatory status and clinical readiness. Available therapies should be selected according to phenotype, organ involvement, efficacy, and safety, whereas investigational and experimental approaches require further evaluation. Major gaps concern predictive biomarkers, direct comparisons, optimal sequencing, long-term safety and durability, and validated patient selection criteria.